Synthesis, characterization and antibacterial study of thiadiazole derivatives. - KRISHNAKANT T. WAGHMODE; VISHAL U. JADHAV (International Journal of Pharma and Bio Sciences, 2017)
Thiadiazoles are five membered heterocycles containing two nitrogen and one sulphur atom. 3,4-dihydropyrimidin-2(1H)-thione is pharmacologically active compound that has been shown to possess various biological activities. In the present study, some Schiff bases of 1,3,4-thiadiazole derivatives of 3,4-dihydropyrimidin-2(1H)-thione are prepared by conventional as well as by microwave heating method and studied for their antibacterial activities. Cyclocondensation of substituted benzoic acid and thiosemicarbazide in presence of POCl3 under reflux condition gave amino thiadiazole derivatives. Various amino thiadiazoles on further condensation with dihyropyrimidin-2-thione gave final product. The structure of the synthesized compounds is confirmed by IR, NMR and Mass spectra. Synthesized compounds are tested for their antibacterial activities. All the synthesized compounds posses moderate antibacterial activity against E. coli and S. aureus bacteria.